Why Academic Quality in Higher Education Declines - Volker Meier; Ioana Cosmina Schiopu (Center for Economic Studies and ifo Institute (CESifo), 2015)
We investigate the choice of quality, or academic content, in higher education in a two-sector model. Individuals are differentiated according to their cost of acquiring human capital. A higher academic quality increases productivity upon training, but is also associated with higher cost of acquiring skill. We consider both a differentiated university system in which quality is tailored to the individual need, and a uniform quality system being politically determined. The former yields a higher income dispersion. Average quality decreases under both systems when the skill premium increases. Moving from a single stage to a two-stage scheme reduces quality in the first stage and increases quality in the second stage. Increasing differentiation in higher education can decrease student effort and skill of medium ability types.
Keywords: I21; I23; I28; J24; 330; higher education; enrollment; quality; higher education systems